Racemic Salsolinol and its Enantiomers Act as Agonists of the μ-Opioid Receptor by Activating the Gi Protein-Adenylate Cyclase Pathway - Berríos-Cárcamo, Pablo; Quintanilla, María E.; Herrera-Marschitz, Mario; Vasiliou, Vasilis; Zapata-Torres, Gerald; Rivera-Meza, Mario (Frontiers in Behavioral Neuroscience, 2017)
Background. Several studies have shown that the ethanol-derived metabolite salsolinol can activate the mesolimbic system, suggesting that salsolinol is the active molecule mediating the rewarding effects of ethanol. In vitro and in vivo studies suggest that salsolinol exerts its action on neuron excitability through a mechanism involving opioid neurotransmission. However, there is not direct pharmacologic evidence showing that salsolinol activates opioid receptors. Methods. The ability of racemic (R/S)-salsolinol, and its stereoisomers (R)-salsolinol and (S)-salsolinol, to activate the µ-opioid receptor was tested in cell-based (light-emitting) receptor assays. To further characterizing the interaction of salsolinol stereoisomers with the µ-opioid receptor, a molecular docking study was performed using the crystal structure of the µ-opioid receptor. Results. This study shows that salsolinol activates the µ-opioid receptor by the classical G protein-adenylate cyclase pathway with an EC50 of 2 x 10-5 M. The agonist action of salsolinol was fully blocked by the µ-opioid antagonist naltrexone. The EC50 for the purified stereoisomers (R)-salsolinol and (S)-salsolinol were 6 x 10-4 M and 9 x 10-6 M respectively. It was found that the action of racemic salsolinol on the µ-opioid receptor did not promote the recruitment of β-arrestin. Molecular docking studies showed that the interaction of (R)- and (S)-salsolinol with the µ-opioid receptor is similar to that predicted for the agonist morphine. Conclusions. It is shown that (R)-salsolinol and (S)-salsolinol are agonists of the µ-opioid receptor. (S)-salsolinol is a more potent agonist than the (R)-salsolinol stereoisomer. In silico analysis predicts a morphine-like interaction between (R)- and (S)-salsolinol with the µ-opioid receptor. These results suggest that an opioid action of salsolinol or its enantiomers is involved in the rewarding effects of ethanol.